PENGARUH AKUNTABILITAS PUBLIK, TRANSPARANSI LAPORAN KEUANGAN, KOMITMEN ORGANISASI DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP PENGELOLAAN KEUANGAN DESA (Studi Empiris Pada Desa-Desa di Kecamatan Concong, Kecamatan Kempas dan Kecamatan Keritang Kabupaten Indragiri Hilir) - Alfiani, Rahmah; M, Rasuli; Supriono, Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aim to examine and to analyze the effect of public accountability, financial report transparency, organizational commitment and the quality of human resources on village financial management. The public accountability variable uses five indicators, namely legal accountability, process accountability, program accountability, policy accountability and financial accountability. The variable of financial report transparency uses four indicators, namely planning, implementation, supervision and accountability. The variable of organizational commitment uses three indicators, namely affective, sustainability and normative. The variable of human resource quality uses three indicators, namely knowledge, skills and attitudes. Meanwhile, the village financial management variable uses five indicators, namely planning, implementation, administration, reporting and accountability. This research includes quantitative research. The total population in this study were 128 village officials in the villages of Concong, Kempas and Keritang, Indragiri Hilir Regency. The sampling technique used was purposive sampling. Data measurement scale with Likert scale. The hypothesis were examined with multiple regression analysis approach and the statistical program used was SPSS 25. The results of this study indicate that public accountability, financial report transparency, organizational commitment and the quality of human resources have a direct and significant effect on village financial management.Keywords: Village Financial Management, Public Accountability, Transparency of Financial Statement, Organizational Commitment and Quality of Human Resources.